Job stress and project performance among construction company in Terengganu - Mohammad Ikwan, Abdullah (2015)
This paper aims to examine the relationship between job stress and project performance. Job stress has been measured by conflict at work, workload and work environment .The previous study concludes that all stressor have negative impact to project performance. Today, the problem has become growing and spreading like wildfire and the organizations lose much money. Meanwhile, for most organization project performance refers to simply to task aspects such as the level of quality of work in the project. Generally, a few common criteria for measuring the level of project performance like the time,cost and quality of the project. All of the decisions made by a project manager regarding the control of the project duration and the effectiveness of the planned schedule and the control the project expanses are crucial to assessing the overall project performance. To study more about the effect of job stress to the project performance, the respondent was selected sample based random sampling method and questionnaires were collected from the previous study or research. This study results that stress is negatively related to project performance, which support by ( Caplan ,1991) and (Keller ,1975) result. This resulted the importance of project performance and find the solution to adapt this problem for successful firm or organization in future.